Punophemisms: Language Use in Ghanaian Hiplife Songs - Avevor, Anita; Polley, Innocentia (Universitas Sanata Dharma, 2023)
This paper is based on how the youth, especially the Ghanaian hiplife musicians manipulate language through the usage of pun to convey messages to their listeners without necessarily sounding vulgar. It focused on the communication of such words which are considered inappropriate and yet must be spoken of, and how young musicians of Ghana try to use these words in songs so they are not seen as sounding profane or disrespectful. In order to find out how this phenomenon takes place, a number of such linguistic items which give their songs an air of style were analysed in some selected Ghanaian songs. The researchers studied the usage of pun by Ghanaian songsters as a mean of euphemising their speech. Related literature on the phenomenon was reviewed and the topic examined through the lenses of Relevance Theory. The data for this research was drawn from songs of young Ghanaian songsters and the research design was a case study. The research employs the descriptive qualitative approach in the analysis of data. The study was basically into the description of data in some selected Ghanaian songs, and the primary data was the internet where selected songs were downloaded for transcription. In this research, there emerged the term punophemisms to explain and define how pun can be used as euphemism.